Isaiah's Christ in Matthew's Gospel (SNTS MS123), Richard Beaton - Eloff, Mervyn (Neotestamentica, 2005)
There are two reasons why Richard Beaton’s monograph rewards careful, albeit somewhat demanding study. The first, though secondary reason, is that at the methodological level, the book provides a model for aspirant researchers and writers. The work comprises a published form of a Cambridge doctoral dissertation, undertaken while resident at Tyndale House. It clearly reflects the virtues of concentrated time and access to good library resources for quality research.